Comparison of ANFIS and FLC as Charging Battery Based on Zeta Converter - Febian, Enggar Bima Ihza; Rakhmawati, Renny; Suhariningsih, Suhariningsih (INTEK: Jurnal Penelitian, 2022)
Solar energy is an unlimited source of energyand its availability will never run out. It can be converted into asupply of electrical energy. And saved into battery throughconverter. There are many people who convert solar energy intoelectrical energy. Unfortunately, when stored in the battery, it isstill necessary to adjust the output voltage of the converter. So, itis need a controller to do it. To solve the problem, we proposeFuzzy Logic Controller (FLC) and Adaptive Neuro FuzzyInference System (ANFIS) control to adjust output voltage whilethe input voltage is fluctuative. We will compare which twocontrollers are better. We used the constant voltage method, andafter we ran the simulation, we got ANFIZ better than FLC.Because we get setting point faster when using ANFIZ. Theresult, it need time 0,04s to get setting point on output voltage